Comparative study into facial sebum level, pore size, and skin hydration between oily-skinned and dry-skinned Thai women - Kunlawat Thadanipon (2020)
© 2019 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd Background: Subjective facial skin type is most frequently determined by the amount of sebum, which showed trends across subjective skin types in most previous studies while not in some. This study was conducted to evaluate the associations among subjective skin type, amount of sebum, stratum corneum hydration, and pore size in Thai women. Methods: Sixty-two healthy women with either self-described subjective oily or dry skin type were included and casual sebum level (CSL), sebum excretion rate (SER), clinical pore size score, mean pore area, and stratum corneum hydration were measured at several facial sites. Correlation coefficients between amount of sebum and other parameters were estimated. Results: Casual sebum level and sebum excretion rate were significantly higher in oily-skinned than dry-skinned group by 1.6-2.1 times. Mean pore area and clinical pore size score were not different between the 2 groups, nor did they correlate with CSL or SER. Corneometry was shown to be significantly higher in dry-skinned than oily-skinned group. Significant, negative correlations between corneometry and CSL were also found. Conclusion: The subjective facial skin types were consistent with the amount of sebum, but not pore size or corneometry, among Thai women.